Microelemental characterisation of Aboriginal Australian natural Fe oxide pigments. Issue 17 (7th September 2015) - Popelka-Filcoff, R. S.; Lenehan, C. E.; Lombi, E.; Donner, E.; Howard, D. L.; de Jonge, M. D.; Paterson, D.; Walshe, K.; Pring, A.
<x xml:space="preserve">Abstract</x> This manuscript presents the first comprehensive microcharacterisation of Fe oxide minerals used in Aboriginal Australian mineral pigments.